GAMBARAN PERILAKU PENGONTROLAN TEKANAN DARAH PENDERITA HIPERTENSI DI PUSKESMAS SELAMA PANDEMI - Selvira Efiskha; Herlina Herlina; Agrina Agrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Hypertension is the most common disease suffered by the people of Indonesia. Hypertension in also called the silent kill because the patient does not know he has hypertension until he has blood pressure checked. This study aims to  find out the description of blood pressure control behavior in hypertensive patients at the puskesmas during the pandemic. This study uses a descriptive design with a cross-sectional approach. The sample in this study was 87 respondents taken using the purposive sampling technique. The questionnaire used in this study has been tested for validity and reliability. The population of this study amounted to 622 people, data analysis is univariate. The results found that from 87 respondents, Blood pressure control behavior was categorized as good as many as 46 people (52.9%). The conclusion of this study is that the behavior of hypertension sufferers in controlling blood pressure is quite good. In this study, hypertension sufferers have started to change their daily lifestyle into a healthy lifestyleKeywords: Blood Pressure, Controlling Behavior, Hypertension